Learning European Languages in Russia and Belarus: Trends and Prospects - Khalevina, Svetlana N.; Sukhorukova, Daria V.; Belozerova, Ekaterina Yu.; Zvereva, Ekaterina V.; Sedova, Tatiana V. (Journal of Ecohumanism, 2024)
This article “Learning European Languages in Russia and Belarus: Trends and Prospects” is a research paper devoted to the competitiveness of European languages ​​in the context of the recent trend of Russia and Belarus turning to the East. The purpose of the research is to establish the demand for the main European languages ​​in modern geopolitical realities. The article touches upon both the historical context of the issue and includes a thorough analysis (supported by statistical data and questionnaires) of the demand for European languages ​​in the stated conditions.